Insights into parental behavior: Patterns of self-medication with antibiotics for child health - Shishir Kumar; Shivani Agrawal; Tajwar Yasmeen; Setu Sinha (Tungs’ Medical Journal, 2025)
Background: The alarming trend of parents self-medicating their children with antibiotics, fueled by easy access to medications and a lack of awareness of the potential consequences, is a critical health concern. Objectives: This study aimed to clarify parents’ behavior toward self-medication of children with antibiotics. Methods: This was a cross-sectional study including parents having children aged <12 years conducted in the community under the Urban Health Training Center of Indira Gandhi Institute of Medical Sciences, Patna, Bihar, India, over 12 months. Participants were chosen through simple random sampling and interviewed using a questionnaire created by the authors. Data were analyzed using logistic regression analysis. Results: A total of 173 parents were included in this study. The prevalence of self-medication was 31.8%. The prevalence of self-medication was higher among mothers than fathers and among parents aged 30–39 years than other age groups. Graduate parents and those who could identify antibiotics correctly were more likely to self-medicate their children (P = 0.002 and <0.001, respectively). Mothers, parents aged ≥40 years, and parents with secondary/higher secondary education were more likely to normally stop giving antibiotics when their children start feeling better. Postgraduate parents (P < 0.001) and those having a family member in the medical field were more likely to keep antibiotic stock at home for later use (P < 0.001). Most parents in all age groups reported waiting 1–2 days before starting antibiotics. The most common reasons for self-medication were minor illness and previous experience with similar symptoms. Conclusion: The insufficient understanding of medicines among parents is a serious concern. Interventions to improve parents’ awareness of antibiotic misuse, resistance, and adverse effects associated with self-medication must be implemented on a large scale.